2018
DOI: 10.1029/2018gl078589
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Near‐Earth Magnetotail Conditions at Substorm and Pseudosubstorm Onsets

Abstract: While a substorm involves auroral poleward expansion after initial brightening, a pseudosubstorm (pseudobreakup) subsides without progressing to poleward expansion. To understand what makes this difference, we studied near‐Earth magnetotail conditions at a pseudosubstorm onset and the subsequent substorm onset, using multipoint Time History of Events and Macroscale Interactions during Substorms spacecraft data. In the present event, near‐Earth magnetic reconnection possibly occurred before initial brightening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Figure 3). Similar relation of plasma sheet β to pseudobreakups and substorms was recently found for a single event study of the near‐Earth magnetotail conditions during fast ion flows that originated from X GSM <−21 R E (Miyashita et al, 2018). That is, despite differences in the dipolarization front formation and substorm scenarios between the near‐Earh BICI mechanism and more tailward reconnection events (Angelopoulos et al, 2008; Nagai et al, 2005; Petrukovich et al, 2009), the requirement of higher β eq may well be common for all substorm models.…”
Section: Relevance To Magnetosphere‐ionosphere Couplingsupporting
confidence: 80%
“…Figure 3). Similar relation of plasma sheet β to pseudobreakups and substorms was recently found for a single event study of the near‐Earth magnetotail conditions during fast ion flows that originated from X GSM <−21 R E (Miyashita et al, 2018). That is, despite differences in the dipolarization front formation and substorm scenarios between the near‐Earh BICI mechanism and more tailward reconnection events (Angelopoulos et al, 2008; Nagai et al, 2005; Petrukovich et al, 2009), the requirement of higher β eq may well be common for all substorm models.…”
Section: Relevance To Magnetosphere‐ionosphere Couplingsupporting
confidence: 80%
“…Since the width of dipolarization fronts may be related to the maximum ion outflow speed in the reconnection jet (Arnold et al, ), the azimuthal size of the corresponding ionospheric current system may also depend on the reconnection jet speed. Reconnection jets with different speed (or alternatively dipolarization fronts with different width) could lead and contribute to pseudo‐breakups and small or global substorms (Miyashita et al, ; Nakamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, such auroral activity is often seen poleward of the most equatorward arc. Miyashita et al () and Motoba et al () presented pseudosubstorm events that were followed by a substorm. Their all‐sky imager data clearly showed that an auroral onset arc developed into wave‐like structure after initial brightening but did not proceed to poleward expansion for the pseudosubstorms, while poleward expansion occurred for the substorms.…”
Section: Introductionmentioning
confidence: 99%